Efficient NO reduction by carbon-deposited CaO in the carbonation step of calcium looping for the CO2 capture. Issue 10 (22nd July 2021) - Zhang, Wan; Qian, Yuqi; Li, Yingjie; He, Zirui; Zhao, Jianli
Abstract : Carbon-deposited CaO realizes efficient NO removal and CO2 capture in carbonator of calcium looping. Abstract : A novel strategy aimed at combining de-NO x with calcium looping for CO2 capture is proposed in this work. In this strategy, hot calcined CaO from the calciner is utilized for biomass pyrolysis to generate syngas and form carbon-deposited CaO (C-CaO). NO is subsequently reduced by the carbon deposited under the catalysis of CaO, while CO2 is captured by CaO in the carbonation step of the calcium looping. In this work, the NO reduction performance of C-CaO in the carbonation step of calcium looping was investigated in a bubbling fluidized bed reactor. C-CaO possesses a considerably high NO reduction performance. Tight adhesion between carbon deposits and CaO significantly improves the catalysis of CaO toward the NO reduction, resulting in an increase in NO reduction efficiency from 58% to 100%. High pyrolysis temperature of 750–800 °C and pine to CaO mass ratio of 3.2 : 16 are beneficial to the formation of carbon deposits. The short pyrolysis duration of 10 min leads to a high activity of C-CaO for the NO reduction. Although O2 continually consumes carbon deposits and the sintering of CaO declines its activity, C-CaO still possesses excellent NO reduction performance before CaO is mostly carbonated or carbon being burned out. Finally, C-CaO realizes a NO reduction efficiency of 100%, while achieving a CO2 capture efficiency above 80% in the carbonation step in the first 5 cycles. Fresh sorbents should be added to the carbonator for efficient CO2 capture and NO removal. This method unites efficient NO reduction with CO2 capture in calcium looping, realizing simultaneous control of pollutants in coal-fired power plants.